Executives’ gender pay gap and financing constraints - Fernandes, Ana P. (2021)
This paper investigates the effect of financing constraints following the 2008-9 financial crisis on executives’ gender inequality. We use linked employer-employee data for the universe of private sector firms in Portugal, and exploit pre-crisis variation in external finance dependence across industries for identification. We find that the crisis had a positive effect on female executives’ pay in exposed firms. Firms in financially more constrained industries reduce the gender pay-gap and increase the share of females in executive positions after the crisis. At the worker-level, females in exposed industries are more likely to be promoted to executive and less likely to be demoted. We discuss channels and interpretations for the effects. Our results are consistent with female managerial characteristics, such as attitudes toward risk, being more valued after the crisis in exposed firms. A reduction in preference-based discrimination cannot be discounted.